Fetal Outcomes in Patients with Isolated Oligohydramnios at Term Presenting to a Tertiary Care Hospital - Noreen Khattak; Kousar Robeen; Mehwish Zeb; Sajida Riaz (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: To evaluate fetal outcomes in term pregnancies complicated by isolated oligohydramnios at a tertiary care hospital. METHODOLOGY: This descriptive cross-sectional study was conducted in the Obstetrics and Gynaecology Department of Khyber Teaching Hospital, Peshawar, from March to September 2020. A total of 208 patients were selected using a non-probability consecutive sampling method with a 95% confidence interval and a 6% margin of error. Inclusion criteria: women of any parity and gravidity with singleton pregnancy, AFI ? 5 cm, gestational age 36–40 weeks, and intact membranes. Exclusion criteria: lack of consent, ruptured membranes, medical disorders, IUGR, fetal anomalies, and multiple pregnancies. AFI was measured by summing the vertical diameters of the largest amniotic fluid pockets in four uterine quadrants. Data on maternal and fetal outcomes were recorded and analyzed using SPSS Version 23.0, with a p-value < 0.05 considered significant. RESULTS: In this study of 208 patients, 12% were aged 15–25 years, and 88% were 26–35 years. Gestational age was 36–38 weeks in 72% and 39–40 weeks in 28%. Primipara accounted for 13%, while 87% were multipara; 15% were primigravida and 85% multigravida. BMI was 25 kg/m² in 42% and >25 kg/m² in 58%. Low APGAR scores were observed in 17% of cases, and 8% required admission to the neonatal intensive care unit. CONCLUSION: In pregnancies complicated by oligohydramnios at term, 17% of neonates had low APGAR scores, and 8% required NICU admission at a tertiary care hospital.